System Dynamic Approach to Improve Emergency Response in Humanitarian Logistics in Indonesia - Sundara, Gregorios Yogas; Ariningsih, Paulina Kus (Institute of Research and Community Outreach - Petra Christian University, 2020)
Volatile and vulnerable conditions during disaster relief cause many problems on the coordination of aid replenishments. Research states that partnership improves coordination thus reducing the uncertainty condition along supply chain including in replenishment. This paper aims to fulfill the research gap on examining the impact of partnership in the disaster relief process. Dynamic characteristics model of this case was built by modifying the beer distribution game through Vensim PLE Plus. Model had been validated and verified with the West Java Regional Disaster Management Authority (BPPD). The simulation was run for for two types of product: repetitive demand (food package) and one-time demand (blanket). Total cost, bullwhip effect, and total distribution time for each scenario are then compared. The simulation results show that the proposed scenario, which is developed based on the usage of blockchain on the partnership system, can reduce the total distribution time for about 43% for blanket and 27% for food package. Meanwhile, the total cost for blankets can be reduced for about 29% and 13% for food packages. But on the other side, the partnership system had aggravated the bullwhip effect. Some future potential researches are also proposed in this study.